TRAINING OF ENGINEERING EDUCATORS AND ADDITIONAL PROFESSIONAL EDUCATION SYSTEM AS AN INTEGRATIVE BASIS FOR RESEARCH UNIVERSITY - Vasiliy G. Ivanov (Высшее образование в России)
The paper presents some results and prospects of development of the contemporary institution for additional professional education. The structure integrates a comprehensive approach to human resourcing of the engineering university on the basis of additional professional programs (professional development) for educators and industry community of the real sector of the economy. The experience of a research university in the interaction with industry in additional professional training (professional development) is analyzed.